Cytotoxic edema at onset in West syndrome of unknown etiology: A longitudinal diffusion tensor imaging study. (8th January 2018) - Ogawa, Chikako; Kidokoro, Hiroyuki; Fukasawa, Tatsuya; Yamamoto, Hiroyuki; Ishihara, Naoko; Ito, Yuji; Sakaguchi, Yoko; Okai, Yu; Ohno, Atsuko; Nakata, Tomohiko; Azuma, Yoshiteru; Hattori, Ayako; et al.
Summary: Objective: To clarify longitudinal changes in white matter microstructures from the onset of disease in patients with West syndrome (WS) of unknown etiology. Methods: Diffusion tensor imaging (DTI) was prospectively performed at onset and at 12 and 24 months old in 17 children with WS of unknown etiology. DTI was analyzed using tract‐based spatial statistics (TBSS) and tract‐specific analysis (TSA) of 13 fiber tracts, and fractional anisotropy (FA) and mean diffusivity (MD) were compared with those of 42 age‐matched controls. Correlations of FA and MD with developmental quotient (DQ) at age 24 months were analyzed. Multiple comparisons were adjusted for using the false discovery rate ( q ‐value). Results: TBSS analysis at onset showed higher FA and lower MD in the corpus callosum and brainstem in patients. TSA showed lower MD in bilateral uncinate fasciculi (UF) (right: q < 0.001; left: q = 0.03) at onset in patients. TBSS showed a negative correlation between FA at onset and DQ in the right frontal lobe, whereas FA at 24 months old exhibited a positive correlation with DQ in the diffuse white matter. MD for bilateral UF at 24 months old on TSA correlated positively with DQ ( q = 0.04, both). Significance: These findings may indicate the existence of cytotoxic edema in the immature white matter and dorsal brainstem at onset, and subsequent alterations in the diffuse white matter in WS of unknown etiology. Microstructural development in the UF might play important roles in cognitive development in WS.